Survey Penerimaan Konsumen dan Uji Iritasi terhadap Sediaan Gel Masker Peel-Off Batang Pisang (Musa paradisiaca L.) dan Bunga Widuri (Calotropis gigantea L.) - Fitria Megawati; Ni Luh Kade Arman Anita Dewi; Ni Putu Dewi Agustini; I Putu Tangkas Suwantara; Ni Made Sintia Dewi (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Peel-off gel masks made from extracts of banana stem (Musa paradisiaca L.) and widuri flower (Calotropis gigantea L.) are natural cosmetic products that contain flavonoids, a secondary metabolite that acts as an antioxidant. The evaluation by consumers is important to understand the level of product acceptance and preference in the market. This study aims to evaluate consumer acceptance of peel-off gel masks made from banana stem and widuri flower extracts, using a quantitative descriptive survey. The sample was collected using an accidental sampling technique from panelists aged between 20 and 40 years old at Universitas Mahasaraswati Denpasar. The survey was conducted through a Google Form that contained questions about consumer preferences (hedonic test) for aroma, viscosity, texture, color, stickiness, and overall product. A total of 40 panelists participated in the hedonic test, while the irritation test was conducted on 9 panelists to observe the possibility of redness or itching reactions on the skin after use. The banana stems peel-off gel mask scored 21.1 in the hedonic test, while the widuri flower peel-off gel mask scored 20.3. The results indicate that the banana stem peel-off gel mask was accepted by 84.4% of the participants in the hedonic test, while the widuri flower peel-off gel mask was accepted by 81.5% of the participants. The irritation test results indicate that neither type of peel-off gel mask caused any irritation after use. Panelists preferred the banana stem peel-off gel mask over the widuri flower peel-off gel mask, with a score of 21.1 and a percentage of 84.4%. Both types of peel-off gel masks are safe to use.